Design, synthesis, molecular modelling, and biological evaluation of novel substituted pyrimidine derivatives as potential anticancer agents for hepatocellular carcinoma - Naglaa Mohamed Ahmed; Mahmoud Youns; Moustafa Khames Soltan; Ahmed Mohammed Said (Taylor & Francis Group, 2019)
New anticancer agents are highly needed to overcome cancer cell resistance. A novel series of pyrimidine pyrazoline-anthracene derivatives (PPADs) (4a-t) were designed and synthesised. The anti-liver cancer activity of all compounds was screened in vitro against two hepatocellular carcinoma (HCC) cell lines (HepG2 and Huh-7) as well as normal fibroblast cells by resazurin assay. The designed compounds 4a-t showed a broad-spectrum anticancer activity against the two cell lines and their activity was more prominent on cancer compared to normal cells. Compound 4e showed high potency against HepG2 and Huh-7 cell lines ((IC50=5.34 and 6.13 μg/mL, respectively) comparable to that of doxorubicin (DOX) activities. A structure activity relationship (SAR) has been investigated and compounds 4e, 4i, 4m, and 4q were the most promising anticancer agents against tested cell lines. These compounds induced apoptosis in HepG2 and Huh-7 cells through significant activation of caspase 3/7 at all tested concentrations. In conclusion, 4e could be a potent anticancer drug.